(untitled) (Annals of Medical Research, 2021)
Aim: Arthroscopic visualization of the knee medial compartment can be challenging in tight knees and undesired chondral damage can occur during instrumentation in these cases. In order to achieve thorough examination of the medial meniscus and to avoid complications, pie crusting of medial collateral ligament (MCL) has been described, which provides opening of the medial joint space. However, concerns about over releasing and instability still remain. Moreover, the reliability and effectively of the pie-crusting technique has not been studied widely. In this study, we aimed to investigate the advantages and possible complications of percutaneous releasing of medial collateral ligament in medial compartment arthroscopy.Material and Methods: A total of 320 arthroscopic surgeries performed between 2014 and 2017 were reviewed retrospectively and 28 patients who underwent partial meniscectomy or repair by pie crust technique were included in the study. Mean follow up was 18 (6-40) months. Patients were evaluated clinically with the Lysholm score and Tegner score. Additionally, joint balance, valgus instability, pain or tenderness at the MCL region and numbness at the medial side of the joint was noted.Results: On physical examination, during valgus stress at 30° of knee flexion, only one patient showed Grade 1 laxity; however, no patients had subjective valgus laxity at the final follow-up. Furthermore, there was no pain or tenderness over the MCL and there were no signs of saphenous nerve or vein injury in any of the patients.Conclusion: Pie-crusting of the medial collateral ligament is an effective and reliable technique which provides enough space for visualization and instrumentation of the medial compartment, particularly in tight knees.Keywords: Pie crust; knee arthroscopy; knee mcl; percutaneous release.